2000
DOI: 10.3184/030823400103167165
|View full text |Cite
|
Sign up to set email alerts
|

Four new sesquiterpenoids from the soft coral Nephthea chabrollii

Abstract: Chemical examination of the soft coral Nephthea chabrolii collected from the Mandapam coast in the Gulf of Mannar, afforded nine sesquiterpenoids of which four (1–4) are new. The structures of the new compounds (1–4) have been established by the interpretation of spectral data (UV, IR, 1H NMR, 13C NMR, 1H-1H COSY, NOESY and mass) and chemical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…Compound 2, a white amorphous powder, exhibited a molecular ion peak M þ at m/z 292.1310 (calc. 292.1311) in the HR-EI-MS, which is consistent with the molecular formula C 16 (Table). The C-atom signals at d(C) 168.9 (C(12)), 137.9 (C(11)), 11.0 (C(13)), 144.8 (C (7)), and 139.1 (C(8)), were undoubtedly assigned to an a,b-unsaturated a-methyl-g-lactone ring.…”
Section: Sesquiterpenoids From the Resinous Exudates Of Commiphora Opsupporting
confidence: 67%
See 2 more Smart Citations
“…Compound 2, a white amorphous powder, exhibited a molecular ion peak M þ at m/z 292.1310 (calc. 292.1311) in the HR-EI-MS, which is consistent with the molecular formula C 16 (Table). The C-atom signals at d(C) 168.9 (C(12)), 137.9 (C(11)), 11.0 (C(13)), 144.8 (C (7)), and 139.1 (C(8)), were undoubtedly assigned to an a,b-unsaturated a-methyl-g-lactone ring.…”
Section: Sesquiterpenoids From the Resinous Exudates Of Commiphora Opsupporting
confidence: 67%
“…Compound 1 was isolated as colorless crystals, which showed a pseudomolecular ion at m/z 301.6 [M þ Na] þ in the positive-ion ESI-MS. Its molecular formula was determined to be C 16 (Table). The presence of an a,b-unsaturated a-methyl-g-lactone moiety was confirmed by the C-atom signals at d(C) 172.8 (C (12)), 129.6 (C(11)), 10.3 (C(13)), 158.7 (C(7)), and 80.9 (C (8) (9) (Fig.…”
Section: Sesquiterpenoids From the Resinous Exudates Of Commiphora Opmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative configuration of 1 was deduced from the 1 H, 1 H coupling constants and the ROESY data. Since HÀC(5) was supposed to be b-oriented [6], HÀC(1) should be a-oriented from the coupling constant between HÀC(1) and HÀC(5) (J ¼ 15.3 Hz). The ROESY cross-peaks HÀC(1)/HÀC(9) and H trans ÀC(14) (trans to C(9))/Me (15) indicated that HÀC(9) was a-oriented, while Me(15) was boriented (Fig.…”
mentioning
confidence: 99%
“…Chemical investigation of soft corals of the genus Nephthea (i.e. N. chabrolii [3][4][5][6][7]14 , N. brassica, 8,15,16 N. tixera, 11 N. albida 11,12 , N. erecta 13 and other Nephthea spp. 9,10,[17][18][19][20][21][22] ) collected from various locations led to the isolation of varied extractives viz., sesquiterpenoids (guaianes 3,4,6,7,8,22 and eudesmanes 17,21 ), tetraprenylbenzenoids 9,21 , diphenylpropane-1,3-diol 10 , sterols (24-methylenecholesterols [11][12][13][14][15][16] ) and diterpenoids (bicyclic 6,22 , brassicolides, 8 xeniaphyllanes 17 , and cembranes [18][19][20]23,24 ).…”
Section: Introductionmentioning
confidence: 99%